Obstructive sleep apnea and its effects on cardiovascular diseases: a narrative review - Rivas, Marcella (Anatol J Cardiol, 2016)
Obstructive sleep apnea (OSA) occurs in 5%-14% of adults but is often undiagnosed. Apneas cause acute physiological changes, including alveolar hypoventilation and pulmonary artery vasoconstriction; they also promote chronic vascular disease secondary to increased platelet adhesiveness, endothelial dysfunction, and accelerated atherosclerosis. The Sleep Heart Health Study demonstrated that OSA is a risk factor for stroke and that an increase of 1 unit in the apnea-hypopnea index increases stroke risk by 6% in men. Patients with OSA frequently have atrial fibrillation (AF). Patients with OSA and AF have an increased incidence of stroke compared with patients with only OSA. The treatment of OSA with CPAP reduces the incidence of stroke and decreases the recurrence rate of AF in patients undergoing pulmonary vein ablation procedures. Undertreated OSA has the potential to complicate the postoperative course of patients undergoing cardiac surgery and increase the frequency of arrhythmias and ischemic events. However, one prospective study demonstrated that OSA did not increase complications during the first 30 days following surgery but increased complications during the long-term follow-up. OSA is associated with increased atherosclerotic coronary disease and the development of coronary events and congestive heart failure. In summary, patients with OSA have an increased frequency of stroke and AF The treatment of these patients with CPAP reduces the frequency of stroke and AF recurrence rate in patients with AF undergoing either medical management or invasive procedures. However, well-designed clinical trials are necessary to answer critical questions regarding the management of OSA in patients with cardiovascular diseases.